Lean Maintenance Design to Optimize the Manufacturing Process: A Peruvian Textile Company Case - Cabana, Jacqueline (2024)
In recent years, the textile industry has increased its exports compared to previous years and produces thousands of jobs per year. However, some manufacturing companies in the textile industry experience low efficiency, such as the current textile company under study associated with unplanned machine downtime and idle time. In this sense, this study aims to promote the capacity, productivity, and efficiency of textile companies that manufacture garments. Therefore, a Lean Maintenance model supported by the integration of Lean Manufacturing instruments and techniques such as TPM, 5S, Kaizen is proposed in order to improve machine availability and quality through management metrics. After the implementation of the proposed tool integration, the activities of the operations were standardized, an increase in efficiency was generated, and a favorable change in maintenance metrics was achieved.